2019
DOI: 10.1021/acsami.8b20493
|View full text |Cite
|
Sign up to set email alerts
|

Photostability of Fullerene and Non-Fullerene Polymer Solar Cells: The Role of the Acceptor

Abstract: Recently, the advent of non-fullerene acceptors (NFAs) made it possible for organic solar cells (OSCs) to break the 10% efficiency barrier hardly attained by fullerene acceptors (FAs). In the past five years alone, more than hundreds of NFAs with applications in organic photovoltaics (OPVs) have been synthesized, enabling a notable current record efficiency of above 15%. Hence, there is a shift in interest toward the use of NFAs in OPVs. However, there has been little work on the stability of these new materia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
79
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 105 publications
(83 citation statements)
references
References 56 publications
4
79
0
Order By: Relevance
“…[ 4,16 ] However, studies up to date indicated that the light stability of NFA systems is strongly materials‐dependent. [ 4,17 ] As a general trend, degradation of NFA systems is different compared to those based on fullerene derivatives. For example, J SC degradation as a result of materials incompatibility [ 8,9,18–20 ] or fullerene dimerization [ 21,22 ] has been revealed for several polymer:phenyl‐C 61 ‐butyric acid methyl ester (PCBM) combinations.…”
Section: Figurementioning
confidence: 99%
“…[ 4,16 ] However, studies up to date indicated that the light stability of NFA systems is strongly materials‐dependent. [ 4,17 ] As a general trend, degradation of NFA systems is different compared to those based on fullerene derivatives. For example, J SC degradation as a result of materials incompatibility [ 8,9,18–20 ] or fullerene dimerization [ 21,22 ] has been revealed for several polymer:phenyl‐C 61 ‐butyric acid methyl ester (PCBM) combinations.…”
Section: Figurementioning
confidence: 99%
“…This is due to the high absorption properties of the WO 3 layer in the short wavelength region. [57,58] In contrast, in the bilayer HTLs devices, At the point where the light passed position 2 (interface of WO 3 layer and BHJ layer), a markedly decreased response and transmittance in the short wavelength region was observed (shown in Figure S19-4-S19-7, Supporting Information). The electric field distributions and transmittances at positions 1, 2, and 3 were determined by analyzing the light irradiated from the top to the bottom of the fabricated devices.…”
Section: Photostability Of Htlsmentioning
confidence: 96%
“…During this process, photodegradation occurred in the NFAs-based BHJ layer due to direct UV-exposure. [57,58] In contrast, in the bilayer HTLs devices, At the point where the light passed position 2 (interface of WO 3 layer and BHJ layer), a markedly decreased response and transmittance in the short wavelength region was observed (shown in Figure S19-4-S19-7, Supporting Information). This is because the WO 3 layer absorbed the short-wavelength light (λ abs = ≈335 nm, shown in Figure S20, Supporting Information).…”
Section: Photostability Of Htlsmentioning
confidence: 96%
See 1 more Smart Citation
“…It seems that NFA‐based devices possess robust storage stability. However, Doumon et al found that NFA with complementary absorption is more likely to deteriorate the device photo‐stability because the increased imbalance of hole and electron mobilities in NFA‐based device would form an undesirable space charge that may obstruct the flow of new charge carriers, leading to less charge extraction during the exposure time and influencing the FF . Recently, Brabec's group further systematically investigated the relationship between molecular structure and photo‐stability, in which the end‐group and side‐chain engineering of the NFA was revealed to have great influence on the photo‐stability of the related devices.…”
Section: Stability Of Active Layer Materialsmentioning
confidence: 99%